IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA INDONESIA KELAS IV DI SDN SINDANGSARI - Saputri, Novia; Sofyan, Deddy; Mulyawati, Yuli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning Indonesian in the context of an independent curriculum invites educators and students to communicate with each other actively. This research uses a qualitative descriptive method which aims to find out how the independent curriculum is implemented in Indonesian language learning. The instruments used in the research show that the implementation of the independent curriculum in class IV Indonesian learnig at SDN Sindangsari has been carried out well. Based on the results of observations and questionnaires given to teachers, students with an average of 48,57%, and school principals/curriculum leaders at 97,7%. Keywords: Indonesian language learning, Implementation of the independent curriculum, pancasila student profile